Análises dos pressupostos de linguagem nos cadernos de formação em língua portuguesa do Pacto Nacional pela Alfabetização na Idade Certa - PNAIC - Resende, Valéria Aparecida Dias Lacerda de [UNESP] (2015)
This research had as its object the Formation Notebooks from the National Pact for Literacy at the Right Age Program ‒ PNAIC from the year of 2013, provided by the Ministry of Education. The research was guided by the thesis that the structure of the Portuguese Language Formation Notebooks from PIAIC, amongst several instances of dialogism that are present in the discursive production, is marked by both linguistic and normative conformability that leads training teachers to do their job with texts that lack interaction with the children. To reach that purpose, I have set as the main objective to analyze concepts of language, explicit or not, in the Portuguese Language Formation Notebooks from Years 1, 2 and 3 of Units 1 and 3 in PNAIC; and as specific objectives: 1) to discuss which conception of language supports the conception of literacy in PNAIC; 2) to show that the theoretical background emerging from the literacy proposal from PIAIC implicates in the extinguishment of language as an activity; and 3) to understand how the conception of writing acquisition from PNAIC would influence in the learners' literacy process.This research dialogues with Mikhail Bakhtin's constructs and it is based on the Historic-Cultural Theory, especially what it says about language and its written register.A qualitative investigation is the approach I used in this research and a documental research was adopted as methodology, according to Le Goff's conceptual bases, having the principles from Carlo Ginzburg's evidentiary paradigm as guidance for the process of choosing and selecting specific utterances from the Formation Notebooks from PIAIC. I organized the data around two thematic blocks: conception of language/literacyand conception of writing,to ensure better both systematization and presentation of the analyses.The results from the first block suggest that PNAIC sees language under the philosophical and the linguistic thinking of abstract...